2019
DOI: 10.4103/tjo.tjo_38_18
|View full text |Cite
|
Sign up to set email alerts
|

A study of endothelial cell count pre- and post-neodymium-doped yttrium aluminum garnet laser iridotomy in subacute angle closure using specular microscope

Abstract: AIM: The aim of this study was to study the effect of neodymium-doped yttrium aluminum garnet (Nd:YAG) laser iridotomy on corneal endothelial cell count in patients with subacute angle closure using specular microscope. MATERIALS AND METHODS: In this prospective study, 50 cases of narrow-angle Grade 1 and Grade 2 (Shaffer gonioscopic grading) visiting the Regional Institute of Ophthalmology, Government Medical College, Amritsar underwent Nd:YAG laser peripheral iridotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Many recent studies with the interest on corneal endothelium in patients with angle closure focused on the effect of laser peripheral iridotomy or phacoemulsification. [29][30][31][32][33][34][35] In PACS, LPI does not appear to cause clinically significant corneal endothelial damage over 1, 3, and 6 years after treatment. [29][30][31][32] However, Bansal et al 33 demonstrated a significant endothelial cell loss at the treated site at a 6 monthfollow-up and suggested that Nd:YAG laser iridotomy may pose hazard to the corneal endothelium in patients with subacute angle closure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many recent studies with the interest on corneal endothelium in patients with angle closure focused on the effect of laser peripheral iridotomy or phacoemulsification. [29][30][31][32][33][34][35] In PACS, LPI does not appear to cause clinically significant corneal endothelial damage over 1, 3, and 6 years after treatment. [29][30][31][32] However, Bansal et al 33 demonstrated a significant endothelial cell loss at the treated site at a 6 monthfollow-up and suggested that Nd:YAG laser iridotomy may pose hazard to the corneal endothelium in patients with subacute angle closure.…”
Section: Discussionmentioning
confidence: 95%
“… 29–35 In PACS, LPI does not appear to cause clinically significant corneal endothelial damage over 1, 3, and 6 years after treatment. 29–32 However, Bansal et al 33 demonstrated a significant endothelial cell loss at the treated site at a 6 monthfollow-up and suggested that Nd:YAG laser iridotomy may pose hazard to the corneal endothelium in patients with subacute angle closure. Studies have also been conducted to evaluate the effect of phacoemulsification on corneal endothelial cells in acute angle closure.…”
Section: Discussionmentioning
confidence: 99%
“…1 With increased age, endothelial cells decrease in fully developed cornea. 2 Basic physiological function performed by corneal endothelium is allowing leakage of nutrients and solutes from the aqueous humor to superficial layers of the cornea and water is pumped in opposite direction actively i.e. from stroma to the aqueous.…”
Section: Introductionmentioning
confidence: 99%